2020
DOI: 10.3390/w12051325
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors Analysis of Taiwan Eutrophicated Reservoirs

Abstract: Treatment cost and quality of domestic water are highly correlated with raw water quality in reservoirs. This study aims to identify the key factors that influence the trophic state levels and correlations among Carlson trophic state index (CTSI) levels, water quality parameters and weather factors in four major reservoirs in Taiwan from 2000 to 2017. Weather (e.g., air temperature, relative humidity, total precipitation, sunlight percentage and cloud cover) and water quality parameters (e.g., pH, chemical oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Several studies reported that values of low transparency can be caused by the presence of high amounts of particles and solutes [40][41][42][43], which in the present study can be supported by the positive Spearman correlation with EC and Mg (EC: R = 0.537, p < 0.05; Mg: R = 0.491, p < 0.05; see Table S3). These results agreed with a study carried out in 50 surface waters in Greece, with the results showing that the lakes most impacted by agricultural and urban activities (highest salt content) had the lowest transparency values [44].…”
Section: Physical Characteristics Of the Reservoirsupporting
confidence: 85%
“…Several studies reported that values of low transparency can be caused by the presence of high amounts of particles and solutes [40][41][42][43], which in the present study can be supported by the positive Spearman correlation with EC and Mg (EC: R = 0.537, p < 0.05; Mg: R = 0.491, p < 0.05; see Table S3). These results agreed with a study carried out in 50 surface waters in Greece, with the results showing that the lakes most impacted by agricultural and urban activities (highest salt content) had the lowest transparency values [44].…”
Section: Physical Characteristics Of the Reservoirsupporting
confidence: 85%
“…where CTSI is the The limitation of the cTSI as reported by the literature is that this model tends to overestimate the trophic levels, partly due to its consideration of the highest productive seasons such as spring and summer in temperate lakes. Consequently, researchers and different studies have adopted different approaches to assess the trophic status of lakes in tropical and subtropical regions and dams that are sensitive to data variability [7].…”
Section: Comprehensive Trophic Status Assessmentmentioning
confidence: 99%
“…However, water in the dam may still be used for irrigation purposes. Putri et al [7] indicated that Africa has adopted the WQI as a monitoring program because it is a strong and reliable index composed of physical, chemical, and biological variables for the determination of water quality. However, this current study contradicts the background provided by Putri et al [7], as there is no known country in Africa that is using the WQI as part of their management practices, except for researchers exploring this option for consideration by decision-makers.…”
Section: Overall Assessment Of Water Quality Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic activities have a direct and indirect impact on the environment [1]. One such type of water pollution is eutrophication, a case of algal bloom caused by increasing levels of nutrients [2,3]. As part of the water pollution management, it is important to detect and manage pollution sources [4,5].…”
Section: Introductionmentioning
confidence: 99%